Do University Libraries in Australia Actively Plan to Protect Special Collections from Disaster?. Issue 4 (2nd October 2018) - Garnett, Johanna; Arbon, Paul; Howard, David; Ingham, Valerie
ABSTRACT: Despite the increasing digitalisation of special collections, Australian university libraries continue to house tangible original works contributing to collective state, national and global heritage. The protection of special collections relates to the international aspirations provided by the Sendai Framework for Disaster Risk Reduction 2015–2030 Priority 3. Currently over five hundred separately grouped university library special collections are recorded in Australia. Globally, there is limited research into university librarian comprehension of how to plan for the protection of special collections. A survey targeted the 35 Australian university libraries identified for inclusion in the study, via the Council for Australian University Librarians (CAUL) database. Eleven (31%) responses qualified for analysis. Of the respondents, the findings include 92% hold tangible special collections as part of their university library collection; 90% do not have a specific plan for the protection of special collections and 90% have experienced a disaster event at some point in their library career. The research concludes that special collections held by Australian universities are at risk and that the role of the university librarian is undervalued in the global efforts to protect cultural and historical heritage in the event of a disaster.